IMPLEMENTASI PRINSIP KEADILAN RESTORATIF PADA PERKARA TINDAK PIDANA KORUPSI - Mandala, Mersy Junedy; Sinurat, Aksi; Manuain, Orpa Ganefo (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Corruption is a social problem that results in efficiency in development, eats away at democracy, and causes economic losses. The handling of cases of criminal acts of corruption in Indonesia with the spirit of recovering state financial losses by the Attorney General's Office faces many problems and weaknesses with very large costs and burdens from the judiciary and correctional institutions that are not in accordance with the concept of criminal procedural law, namely fast, simple and low-cost trials or non-recovery. loss of state finances because the convict chooses to undergo water subsidies rather than paying replacement money. Restorative justice is present as a new paradigm to avoid handling protracted problems, not recovering state financial losses, operations and large handling costs. In practice, the spirit of restorative justice has been widely applied to corruption cases by returning all state financial losses, so cases are not proceeded to court, but it is necessary to regulate the handling of corruption based on restorative justice at every level of legislation as a guide for law enforcement officials.